Predictive Analysis of Cognitive Style and Gender on Junior High School Students’ Mastery of the Pythagorean Theorem - Nur'aini, Khumaeroh Dwi; Natsir, Irmawaty (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2025)
This study investigates the predictive effect of gender and cognitive style on junior high school students’ mastery of the Pythagorean Theorem. A quantitative ex post facto design was applied to 71 eighth-grade students who had previously learned this topic. Mastery was measured using a five-item conceptual test, with a mastery threshold of 72% or higher, based on curriculum competency standards, expert judgment, and assessment guidelines. Gender (0 = female; 1 = male) and cognitive style (0 = FD; 1 = FI) were assessed using the Group Embedded Figures Test (GEFT). Binary logistic regression was employed. Model fit was satisfactory (Hosmer–Lemeshow p = .473), accuracy = 85.9%, and pseudo-R² (Nagelkerke) = 0.671. Cognitive style significantly predicted mastery (OR = 93.62, 95% CI = [10.64, 823.80], p < .001), while gender did not reach significance (OR = 4.12, 95% CI = [0.92, 18.42], p = .064). Findings highlight the need for adaptive learning strategies tailored to students’ cognitive style. Future studies should include additional predictors (e.g., motivation, instructional support) and apply calibration and cross-validation techniques to enhance prediction generalizability.